The christian value of human suffering from the perspective of Max Scheler: a review of the first edition of vom sinn des laides (1916) - Ramírez Patiño, Marisol (2022)
The purpose of the essay is to show in detail a little explored essay by the German philosopher Max Scheler (1874-1928) entitled, On the meaning of suffering (Vom Sinn des Leides). This essay was published after the end of the First World War and until shortly before the death of its author, it was constantly edited and enlarged, which demonstrates his constant interest in the phenomenon of pain and human suffering within his philosophical system. The first version of the essay states that in all times, cultures and religions there is a constant struggle with the question of suffering, its truth, its meaning and, ultimately, with the concrete and real drama of pain itself. This is an inescapable question for any philosophical understanding of man, since it calls for a renewed approach to the fundamental questions about his origin, his meaning and his destiny.